Positive electrode material and preparation method thereof, positive electrode plate, secondary battery and electric device
Patent Information
- Application Number
- CN202280095409.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-16
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2042-12-16
AI Technical Summary
The widely used polycrystalline high-nickel cathode materials have poor cycle stability during deep charge and discharge processes, limiting their commercial applications.
Rare earth elements and/or refractory metal elements are used to modify high-nickel ternary particles to form a fast ion conductor network rich in rare earth metal atoms or a strong bond energy stable structure of refractory metal elements to improve cycle performance.
The cycle stability and structural stability of the cathode material are significantly improved, and the cycle life and storage time are extended.
Smart Images

Figure CN119256407A_ABST
Abstract
Description
Positive electrode material and preparation method thereof, positive electrode sheet, secondary battery and electrical device Technical Field
[0001] The present application relates to the field of batteries, and specifically to a positive electrode material and a preparation method thereof, a positive electrode sheet, a secondary battery and an electrical device. Background Art
[0002] With the goal of carbon neutrality being proposed, developing abundant and low-cost cathode materials to produce high-energy-density batteries remains a significant challenge in meeting the ever-increasing range demands of power-consuming devices such as long-range electric vehicles. High-nickel layered materials, with their high capacity and low cost, are considered one of the most promising cathode materials for lithium-ion batteries. However, the currently widely used polycrystalline high-nickel cathodes generally suffer from poor cycling stability during deep charge and discharge, severely limiting their commercial application. Technical issues
[0003] The present application provides a positive electrode material and a preparation method thereof, a positive electrode plate, a secondary battery and an electrical device, which can improve the cycle stability of the positive electrode material. Technical Solutions
[0004] In a first aspect, the present application provides a positive electrode material, comprising positive electrode material particles, wherein the positive electrode material particles include a matrix and a modifying element, wherein:
[0005] The matrix includes LiNixCoyMnzO2, x≥0.8, y≤0.12, x+y+z=1;
[0006] The modifying elements include rare earth elements and / or refractory metal elements.
[0007] In the technical solution of the embodiment of the present application, the rare earth elements and / or refractory metal elements are used to modify the high-nickel ternary particles, wherein rare earth metal atoms (hereinafter referred to as element A) can enter the surface structure of the positive electrode material, forming an A-rich fast ion conductor network on the surface of the high-nickel ternary particles, isolating the electrolyte, reducing side reactions, and thus improving the cycle performance; refractory metal elements (hereinafter referred to as element B) can enter the high-nickel positive electrode bulk phase, forming a stable structure with strong bond energy, reducing the generation of impurities such as rock salt phase under high pressure, and improving the cycle performance. Thus, by modifying the high-nickel ternary particles with the rare earth elements and / or refractory metal elements, the cycle stability of the positive electrode material can be improved.
[0008] In some embodiments, the rare earth element is at least partially located on the surface of the substrate. When the high-nickel ternary particles are modified with the rare earth element, at least some rare earth metal atoms (hereinafter referred to as element A) can enter the surface structure of the positive electrode material, forming an A-rich fast ion conductor network on the surface of the high-nickel ternary particles, which isolates the electrolyte and reduces side reactions, thereby improving cycle performance.
[0009] In some embodiments, the refractory metal element is at least partially located within the matrix. When the high-nickel ternary particles are modified with the refractory metal element, at least a portion of the refractory metal element enters the high-nickel cathode bulk phase, forming a stable structure with strong bonding energy, reducing the formation of impurities such as rock salt phases under high pressure, thereby improving cycling performance.
[0010] In some embodiments, the rare earth element includes at least one of lanthanum, cerium, praseodymium, neodymium, promethium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium, and lutetium. Modifying the high-nickel ternary particles with these rare earth elements can significantly improve the cycling performance of the high-nickel ternary particles as cathode materials.
[0011] In some embodiments, the rare earth element is lanthanum. Selecting lanthanum to modify the high nickel ternary particles has a more significant effect on improving the cycle performance of the high nickel ternary particles as an electrode positive material, and the modification process is easy to implement.
[0012] In some embodiments, the refractory metal element includes at least one of titanium, zirconium, niobium, vanadium, molybdenum, and tungsten. Modifying the high-nickel ternary particles with these refractory metal elements can significantly improve the cycling performance of the high-nickel ternary particles as cathode materials.
[0013] In some embodiments, the refractory metal element is niobium. Using niobium to modify the high-nickel ternary particles has a more significant effect on improving the cycle performance of the high-nickel ternary particles as electrode positive materials, and the modification process is easy to implement.
[0014] In some embodiments, the modifying element is combined with the matrix by doping. By combining the modifying element with the matrix through doping, the bonding effect between the modifying element and the matrix can be improved, the possibility of the modifying element detaching from the matrix can be reduced, and the modification effect on the high-nickel ternary particles can be guaranteed.
[0015] In some embodiments, the doping mass of the modifying element is 1-10% based on 100% of the mass of the positive electrode material. Controlling the doping mass of the modifying element within the range of 1-10% has a better modification effect on the high-nickel ternary particles and is easy to control costs.
[0016] In some embodiments, the doping amount of the modifying element is 3-5% based on 100% of the mass of the positive electrode material. Controlling the doping amount of the modifying element within this range can significantly improve the modification effect of the high-nickel ternary particles.
[0017] In some embodiments, the LiNixCoyMnzO2 is a single-crystal particle. The use of single-crystal high-nickel ternary particles, with their non-porous and high-strength properties, helps increase the compaction density of the positive electrode material, thereby improving the energy density of the battery. This also helps improve the structural stability and cycling performance of the positive electrode material, and provides better stability under high pressure.
[0018] In some embodiments, the Dv50 of the LiNixCoyMnzO2 is ≥4 μm. By limiting the Dv50 of the high-nickel ternary particles to ≥4 μm, the particle breakage rate during the cycle can be reduced, which is conducive to obtaining a better compaction density, thereby obtaining a positive electrode material with better structural stability and cycle performance.
[0019] In some embodiments, the SPAN of the LiNixCoyMnzO2 is ≥ 1.6. By limiting the SPAN of the high-nickel ternary particles to ≥ 1.6, the particle breakage rate during the cycle can be reduced, which is conducive to obtaining a better compaction density, thereby obtaining a positive electrode material with better structural stability and cycle performance.
[0020] In a second aspect, the present application proposes a method for preparing a positive electrode material, comprising the following steps:
[0021] The modifier is mixed with LiNixCoyMnzO2 and calcined to obtain the positive electrode material; wherein,
[0022] In the LiNixCoyMnzO2, x≥0.8, y≤0.12, x+y+z=1;
[0023] The modifier includes rare earth elements and / or refractory metal elements.
[0024] In the technical solution of the embodiment of the present application, high-nickel ternary particles modified with rare earth elements and / or refractory metal elements can be obtained by mixing and calcining a modifier including the rare earth elements and / or refractory metal elements with LiNixCoyMnzO2, thereby effectively improving the structural stability and cycle performance of the high-nickel ternary particles as battery positive electrode materials.
[0025] In some embodiments, the modifier includes LiXAYBZO(X+3Y+5Z) / 2, LiXAYO(X+3Y) / 2 or LiXBZO(X+5Z) / 2, X≥5, Y≥3, Z≥2, A is any one of lanthanum, cerium, praseodymium, neodymium, promethium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium, and lutetium, and B is any one of titanium, zirconium, niobium, vanadium, molybdenum, and tungsten.
[0026] By using LiXAYBZO(X+3Y+5Z) / 2, LiaAbO(a+3b) / 2 or LiaBcO(a+5c) / 2 as modifiers and mixing them with LiNixCoyMnzO2 for calcination, high-nickel ternary particles modified with rare earth elements and refractory metal elements, high-nickel ternary particles modified with rare earth elements, and high-nickel ternary particles modified with refractory metal elements can be produced respectively. All three methods can effectively improve the structural stability and cycle performance of high-nickel ternary particles as battery positive electrode materials.
[0027] In some embodiments, the calcination temperature is 600-800° C. and the calcination time is 1-3 hours. Under these calcination conditions, the preparation efficiency of the positive electrode material is high.
[0028] In a third aspect, the present application proposes a positive electrode plate, comprising the positive electrode material in the above embodiment or the positive electrode material prepared in the above embodiment.
[0029] In a fourth aspect, the present application proposes a secondary battery comprising the positive electrode sheet in the above embodiment.
[0030] In a fifth aspect, the present application proposes an electrical device comprising the secondary battery in the above embodiment. Beneficial effects
[0031] In the technical solution of the embodiment of the present application, the rare earth elements and / or refractory metal elements are used to modify the high-nickel ternary particles, wherein rare earth metal atoms (hereinafter referred to as element A) can enter the surface structure of the positive electrode material, forming an A-rich fast ion conductor network on the surface of the high-nickel ternary particles, isolating the electrolyte, reducing side reactions, and thus improving the cycle performance; refractory metal elements (hereinafter referred to as element B) can enter the high-nickel positive electrode bulk phase, forming a stable structure with strong bond energy, reducing the generation of impurities such as rock salt phase under high pressure, and improving the cycle performance. Thus, by modifying the high-nickel ternary particles with the rare earth elements and / or refractory metal elements, the cycle stability of the positive electrode material can be improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other relevant drawings can be obtained based on these drawings without paying any creative work.
[0033] FIG1 is a schematic structural diagram of some embodiments of the positive electrode material provided in this application.
[0034] The realization of the objectives, functional features and advantages of this application will be further explained in conjunction with embodiments and with reference to the accompanying drawings. Modes for Carrying Out the Invention
[0035] Below, the embodiments of the positive electrode material and its manufacturing method, positive electrode sheet, secondary battery, battery module, battery pack and electrical device of the present application are described in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0036] The "range" disclosed in this application is defined in the form of a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of a particular range. The range defined in this way can be inclusive or exclusive of the end values, and can be arbitrarily combined, i.e., any lower limit can be combined with any upper limit to form a range. For example, if a range of 60 to 120 and 80 to 110 is listed for a particular parameter, it is understood that a range of 60 to 110 and 80 to 120 is also expected. In addition, if the minimum range values listed are 1 and 2, and if the maximum range values listed are 3, 4, and 5, then the following ranges can all be expected: 1 to 3, 1 to 4, 1 to 5, 2 to 3, 2 to 4, and 2 to 5. In this application, unless otherwise specified, the numerical range "a to b" represents an abbreviation of any real number combination between a and b, wherein a and b are both real numbers. For example, a numerical range of "0-5" indicates that all real numbers between "0-5" are listed herein, and "0-5" is simply an abbreviation for these numerical combinations. Furthermore, stating that a parameter is an integer ≥ 2 is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0037] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0038] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0039] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), indicating that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0040] Unless otherwise specified, the terms "include" and "comprising" used in this application may be open-ended or closed-ended. For example, "include" and "comprising" may mean that other components not listed may also be included or that only the listed components are included.
[0041] Unless otherwise specified, the term "or" is used in this application to be inclusive. For example, the phrase "A or B" means "A, B, or both A and B." More specifically, the condition "A or B" is satisfied if any of the following conditions are met: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0042] Currently, market developments indicate that power batteries are becoming increasingly widely used. They are not only used in energy storage systems such as hydropower, thermal, wind, and solar power plants, but are also widely used in electric vehicles like electric bicycles, electric motorcycles, and electric vehicles, as well as in military equipment and aerospace. As power battery applications continue to expand, market demand is also growing.
[0043] With the goal of carbon neutrality being proposed, developing abundant and low-cost cathode materials to produce high-energy-density batteries remains a significant challenge in meeting the ever-increasing range demands of power-consuming devices, such as long-range electric vehicles. High-nickel layered materials, with their high capacity and low cost, are considered one of the most promising cathode materials for lithium-ion batteries. However, the currently widely used polycrystalline high-nickel cathodes generally suffer from poor cycling stability during deep charge and discharge, severely limiting their commercial application.
[0044] Based on the above considerations, in order to solve the problem that the poor cycle performance of high-nickel positive electrode materials limits their practical application, the inventors conducted in-depth research and designed a scheme to modify high-nickel positive electrode materials by ion doping the high-nickel positive electrode materials to improve their cycle performance.
[0045] Specifically, in some embodiments of the present application, the positive electrode material includes positive electrode material particles, and the positive electrode material particles include a matrix and a modifying element, wherein: the matrix includes LiNixCoyMnzO2, x≥0.8, y≤0.12, x+y+z=1; the modifying element includes a rare earth element and / or a refractory metal element.
[0046] In the technical solution of the embodiment of the present application, rare earth elements and / or refractory metal elements are used to modify the high-nickel ternary particles, wherein the rare earth element (hereinafter referred to as element A) can enter the surface structure of the positive electrode to form an A-rich fast ion conductor network, which can isolate the electrolyte and reduce side reactions, thereby improving the cycle performance; the refractory metal element (hereinafter referred to as element B) can enter the high-nickel positive electrode bulk phase to form a stable structure with strong bond energy, reduce the generation of impurities such as rock salt phase under high pressure, and improve the cycle performance. Thus, by modifying the high-nickel ternary particles with rare earth elements and / or refractory metal elements, the cycle stability of the positive electrode material can be improved; wherein, the high-nickel ternary particles are modified with rare earth elements and refractory metal elements at the same time. Relevant performance tests have shown that its effect is better than that of modification with a single rare earth element or a single refractory metal element, especially in that its cycle life and storage time are better.
[0047] Rare earth elements are a collective term for 17 elements, including lanthanides (La), scandium (Sc), and yttrium (Y). Lanthanides refer to the 15 elements from lanthanum (element 57) to lutetium (element 71) in the periodic table. Theoretically, all rare earth elements can effectively modify the high-nickel ternary particles described in this application. In some embodiments of this application, the rare earth element is a lanthanide element, specifically including at least one of lanthanum, cerium, praseodymium, neodymium, promethium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium, and lutetium. Using these rare earth elements to modify high-nickel ternary particles can significantly improve the cycling performance of high-nickel ternary particles as electrode positive materials.
[0048] In some embodiments of the present application, the rare earth element is lanthanum. The use of lanthanum to modify the high-nickel ternary particles has a more significant effect on improving the cycle performance of the high-nickel ternary particles as electrode positive electrode materials, and the modification process is easy to implement.
[0049] Typical refractory metals include tungsten, tantalum, molybdenum, niobium, hafnium, chromium, vanadium, zirconium, and titanium. Theoretically, any of these metal elements can effectively modify the high-nickel ternary particles described in this application. In some embodiments of this application, the refractory metal element includes at least one of titanium, zirconium, niobium, vanadium, molybdenum, and tungsten. Using these refractory metal elements to modify the high-nickel ternary particles can significantly improve the cycling performance of the high-nickel ternary particles as electrode positive materials.
[0050] In some embodiments of the present application, the refractory metal element is niobium. Using niobium to modify the high-nickel ternary particles has a more significant effect on improving the cycle performance of the high-nickel ternary particles as electrode positive materials, and the modification process is easy to implement.
[0051] In some embodiments of the present application, the rare earth element is at least partially located on the surface of the substrate. When the high-nickel ternary particles are modified with rare earth elements, at least some of the rare earth metal atoms can enter the surface structure of the positive electrode material, forming an A-rich fast ion conductor network on the surface of the high-nickel ternary particles, which serves to isolate the electrolyte and reduce side reactions, thereby improving cycle performance.
[0052] In some embodiments of the present application, the refractory metal element is at least partially located within the matrix. When the high-nickel ternary particles are modified with the refractory metal element, at least a portion of the refractory metal element will enter the high-nickel cathode bulk phase, forming a stable structure with strong bonding energy, reducing the formation of impurities such as rock salt phases under high pressure, thereby improving cycle performance.
[0053] In some embodiments, the modifying element is combined with the matrix by doping. By combining the modifying element with the matrix by doping, the combination effect of the modifying element and the matrix can be improved, the possibility of the modifying element detaching from the matrix is reduced, and the modification effect on the high-nickel ternary particles is guaranteed. Specifically, the above-mentioned doping methods include surface doping and / or bulk doping. When rare earth elements are used as modifying elements, it is surface doping, which is usually coated on the surface of the matrix. When refractory metal elements are used as modifying elements, it is bulk doping, which usually enters the matrix phase. In some embodiments of the present invention, the above-mentioned surface doping and bulk doping can be achieved by mixing and calcining a substance containing the modifying element with a matrix.
[0054] In some specific embodiments of the present application, the modifying element includes a lanthanide element, and the lanthanide element is at least partially located on the surface of the high-nickel ternary particles, which can be regarded as modifying the surface of the high-nickel ternary particles. A atoms enter the surface structure of the positive electrode material to form an A-rich fast ion conductor network, which can isolate the electrolyte and reduce side reactions, thereby improving the cycle performance. The implementation method of using lanthanide elements to modify high-nickel ternary particles can be, for example, LiXAYO(X+3Y) / 2 (X≥5, Y≥3, and X and Y are integers, A is any one of lanthanum, cerium, praseodymium, neodymium, promethium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium, and lutetium) and LiNixCoyMnzO2 high-nickel ternary particles are mixed and calcined.
[0055] In some specific embodiments of the present application, the modifying element includes at least one of titanium, zirconium, niobium, vanadium, molybdenum, and tungsten, and at least a portion of the modifying element is located within the high-nickel ternary particle. This can be considered as modifying the inner layer of the high-nickel ternary particle. The modifying element B enters the high-nickel cathode bulk phase, forming a stable structure with strong bond energy, reducing the formation of impurities such as rock salt phase under high pressure, thereby improving cycle performance. The method of modifying the high-nickel ternary particles using at least one of titanium, zirconium, niobium, vanadium, molybdenum, and tungsten can be, for example, by mixing and calcining LiXBZO(X+5Z) / 2 (X≥5, Z≥2, and X and Z are integers, and B is any one of titanium, zirconium, niobium, vanadium, molybdenum, and tungsten) with LiNixCoyMnzO2.
[0056] In some specific embodiments of the present application, referring to FIG1 , the modifying elements include lanthanide elements and refractory metal elements, wherein the lanthanide metal is at least partially located on the surface of the high-nickel ternary particles. In order to modify the surface layer of the high-nickel ternary particles, A atoms enter the surface structure of the positive electrode to form an A-rich fast ion conductor network, which can isolate the electrolyte and reduce side reactions, thereby improving the cycle performance; the refractory metal element is at least partially located inside the high-nickel ternary particles. In order to modify the inner layer of the high-nickel ternary particles, the modifying element B enters the high-nickel positive electrode bulk phase to form a stable structure with strong bond energy, reducing the generation of impurities such as rock salt phase under high pressure, thereby improving the cycle performance. In this way, through the joint modification of lanthanide elements and refractory metal elements, the overall structure of the high-nickel positive electrode material can be made more stable and the cycle performance can also be more stable. The modification elements include lanthanide elements and refractory metal elements. For example, LiXAYBZO(X+3Y+5Z) / 2 (X≥5, Y≥3, Z≥2, and X, Y, and Z are all integers, A is any one of lanthanum, cerium, praseodymium, neodymium, promethium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium, and lutetium, and B is any one of titanium, zirconium, niobium, vanadium, molybdenum, and tungsten) can be mixed and calcined with LiNixCoyMnzO2.
[0057] SEM and EDS tests were performed on the high-nickel ternary particles of LiNixCoyMnzO2 before and after modification. It was found that element A was concentrated on the surface of the high-nickel ternary particles, and the element deposition was shallow, while element B was incorporated into the bulk phase of the particles, and the element deposition was more obvious. This shows that the modification method provided in this application can successfully achieve the effects of surface modification, internal layer modification or surface / bulk co-doping modification.
[0058] Furthermore, in some embodiments, the doping mass of the modifying element is 1-10% based on the mass of the positive electrode material as 100%. Controlling the doping mass of the modifying element within the range of 1-10% has a better modification effect on the high-nickel ternary particles and is easy to control costs. It is understood that when the modifying element includes element A or element B, the doping amount of the modifying element refers to the doping amount of element A or element B in the high-nickel ternary particles, and when the modifying element includes element A and element B, the doping amount of the modifying element refers to the total doping amount of element A and element B.
[0059] In some embodiments, the doping amount of the modifying element is 3-5% based on 100% of the positive electrode material. Controlling the doping amount of the modifying element within this range can significantly improve the modification effect on the high-nickel ternary particles and enhance the cycling performance.
[0060] In some embodiments of the present application, LiNixCoyMnzO2 is a single crystal particle. The use of single crystal high-nickel ternary particles, with their non-porous and high-strength properties, helps increase the compaction density of the high-nickel cathode material, thereby improving the battery's energy density. This also improves the structural stability and cycling performance of the high-nickel cathode material. Single crystal high-nickel ternary materials exhibit superior high-voltage stability, with an upper voltage limit of ≥4.3V. At a high voltage of 4.3V, the unit cell volume shrinkage of polycrystalline high-nickel is caused by the irreversible H2-H3 phase transition, which inevitably leads to nanocrack formation under highly delithiated conditions. Furthermore, the cathode surface inevitably contacts the electrolyte, leading to severe interfacial reactions. In this application, ion doping accelerates electron / ion conduction and stabilizes the internal lattice structure. Doping elements with strong metal-oxygen (MO) bonds inhibit the migration of transition metal ions (TMs), mitigate structural degradation, and promote Li+ diffusion. Furthermore, the coating of the fast ion conductor network formed by rare earth element modification can improve low-state-of-charge (SOC) kinetics and enhance the power performance of the power battery.
[0061] When high-nickel materials are used as positive electrode materials for batteries, the particle size of the high-nickel materials will also have some impact on the relevant performance of the battery. The following Table 1 shows the relevant performance parameters under different particle sizes.
[0062] Table 1 Performance parameters of LiNixCoyMnzO2 with different particle sizes Particle size Dv50 (μm) Energy density 25℃ 10%SOC DCR 25℃ 2.8~4.3V cycle life 60℃ 4.3V storage (days) 3 high high 1200 280 5 High High 1500 300 10 Moderate High 1650 500
[0063] It can be seen from Table 1 that as the particle size of LiNixCoyMnzO2 increases, the energy density increases slightly, while the DCR, cycle and storage performances improve significantly. In addition, large-particle single crystals are not easy to crack and have good high-voltage stability.
[0064] In some embodiments of the present application, the Dv50 of LiNixCoyMnzO2 is ≥4μm. Among them, Dv50 ≥4μm means that the particle size corresponding to 50% of the particle volume distribution is ≥4μm. In this way, by limiting the Dv50 ≥4μm of the high-nickel ternary particles, large and small particles are tightly packed, which can avoid the accumulation of large particles due to excessive local stress and easier breakage, thereby reducing the breakage rate of the high-nickel ternary particles during the cycle, which is conducive to obtaining a better compaction density, so as to obtain a positive electrode material with better structural stability and cycle performance. Furthermore, in practical applications, a more specific particle size range can be further selected based on Dv50 ≥4μm in combination with the specific performance parameters required by the battery.
[0065] In some embodiments of the present application, the SPAN of LiNixCoyMnzO2 is ≥1.6. Here, SPAN = (Dv90-Dv10) / Dv50, where Dv90 is the particle size corresponding to 90% of the particle volume distribution, Dv10 is the particle size corresponding to 10% of the particle volume distribution, and Dv50 is the particle size corresponding to 50% of the particle volume distribution. By limiting the SPAN of high-nickel ternary particles to ≥1.6, large and small particles are tightly packed, which can avoid excessive local stress in large particles that makes them more likely to break, thereby reducing the particle breakage rate during the cycle, facilitating a better compaction density, and ultimately resulting in a positive electrode material with better structural stability and cycle performance.
[0066] In a second aspect, the present application proposes a method for preparing the positive electrode material in the above embodiment. Specifically, the method for preparing the positive electrode material comprises the following steps:
[0067] A modifier is mixed with LiNixCoyMnzO2 and calcined to obtain a positive electrode material; wherein, in LiNixCoyMnzO2, x≥0.8, y≤0.12, and x+y+z=1; and the modifier includes a rare earth element and / or a refractory metal element.
[0068] In the technical solution of the embodiment of the present application, by mixing and calcining a modifier including a rare earth element (A) and / or a refractory metal element (B) with LiNixCoyMnzO2, the rare earth element and / or refractory metal element can be combined with the LiNixCoyMnzO2 in a doping manner to produce high-nickel ternary particles modified with rare earth elements and / or refractory metal elements, thereby effectively improving the structural stability and cycle performance of the high-nickel ternary particles as battery positive electrode materials.
[0069] In some embodiments of the present application, the rare earth element includes a lanthanide element, specifically including at least one of lanthanum, cerium, praseodymium, neodymium, promethium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium, and lutetium, and the refractory metal element includes at least one of titanium, zirconium, niobium, vanadium, molybdenum, and tungsten. Correspondingly, the modifier includes LiXAYBZO(X+3Y+5Z) / 2, LiXAYO(X+3Y) / 2, or LiXBZO(X+5Z) / 2, where X≥5, Y≥3, and Z≥2, and X, Y, and Z are all integers, A is any one of lanthanum, cerium, praseodymium, neodymium, promethium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium, and lutetium, and B is any one of titanium, zirconium, niobium, vanadium, molybdenum, and tungsten.
[0070] By using LiXAYBZO(X+3Y+5Z) / 2, LiaAbO(a+3b) / 2 or LiaBcO(a+5c) / 2 as modifiers and mixing them with LiNixCoyMnzO2 for calcination, high-nickel ternary particles in which the surface of the high-nickel ternary particles is modified with lanthanide elements, high-nickel ternary particles in which the interior of the high-nickel ternary particles is modified with refractory metal elements, and high-nickel ternary particles in which the surface of the high-nickel ternary particles is modified with rare earth elements and the interior of the high-nickel ternary particles is modified with refractory metal elements at the same time can be prepared respectively. All three methods can effectively improve the structural stability and cycle performance of the high-nickel ternary particles as battery positive electrode materials.
[0071] In some embodiments of the present application, the modifier is LiXAYO(X+3Y) / 2 (X≥5, Y≥3, and X and Y are both integers, A is any one of lanthanum, cerium, praseodymium, neodymium, promethium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium, and lutetium), which is mixed with LiNixCoyMnzO2 and calcined to modify the surface of the high-nickel material. The A atoms enter the surface structure of the positive electrode material to form an A-rich fast ion conductor network, which isolates the electrolyte and reduces side reactions, thereby improving the cycle performance.
[0072] In some embodiments of the present application, the modifier is LiXBZO(X+5Z) / 2 (X≥5, Z≥2, and X and Z are both integers, B is any one of titanium, zirconium, niobium, vanadium, molybdenum, and tungsten), which is mixed with LiNixCoyMnzO2 and calcined to modify the inner layer of the high-nickel material. The B element enters the high-nickel positive electrode bulk phase to form a stable structure with strong bond energy, reducing the generation of impurities such as rock salt phase under high pressure, thereby improving the cycle performance.
[0073] In some embodiments of the present application, the modifier is LiXAYBZO(X+3Y+5Z) / 2 (X≥5, Y≥3, Z≥2, and X, Y, and Z are all integers, A is any one of lanthanum, cerium, praseodymium, neodymium, promethium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium, and lutetium, and B is any one of titanium, zirconium, niobium, vanadium, molybdenum, and tungsten), and after mixed and calcined with LiNixCoyMnzO2, the surface and inner layers of the high-nickel material are simultaneously modified. By co-doping with lanthanide metal elements and B elements, the overall structural stability and cycle stability of the high-nickel material are further improved; at the same time, the surface layer A and Li form a fast ion conductor network, which provides a rapid diffusion channel for lithium ion transmission, thereby further improving the power performance of the battery.
[0074] In some embodiments of the present application, the calcination temperature is 600-800° C. and the calcination time is 1-3 hours. Under these calcination conditions, the preparation efficiency of the positive electrode material is high.
[0075] In addition, in some embodiments of the present application, a method for preparing single crystal LiNixCoyMnzO2 is also provided, and the steps are as follows: first, soluble sulfates of nickel, cobalt, and manganese are prepared into a solution with a total molar concentration of metal ions of 1.0~2.2mol / L according to a certain molar ratio of nickel, cobalt, and manganese ions (for example, 83:12:5), and then a certain concentration of sodium hydroxide solution (concentration of 4~8mol / L) and ammonia water (concentration of 0.1~0.5mol / L) are added in sequence and stirred and mixed, and a coprecipitation reaction is carried out under a nitrogen atmosphere. , the pH value of the coprecipitation reaction is controlled at 9-12 and the reaction temperature is 40-60°C to obtain a hydroxide precursor containing nickel, cobalt and manganese; the prepared precursor is washed and dried, LiOH and KCl fluxes are added, first sintered at 300-500°C for 5-7h, then calcined at 700-900°C for 12-18h, and then annealed in oxygen at 400-600°C for 2-4h to obtain single crystal LiNixCoyMnzO2 (x≥0.8, y≤0.12, x+y+z=1) high nickel ternary material powder.
[0076] In addition, in some embodiments of the present application, taking the modification of LiNixCoyMnzO2 using LiXAYBZO(X+3Y+5Z) / 2 (X≥5, Y≥3, Z≥2, A is lanthanum, and B is niobium) as an example, a more specific implementation method for preparing the positive electrode material is also provided, and the steps are as follows: stoichiometric LiNO3, La(CH3COO)3 and C4H4NNbO9·nH2O are used as materials for preparing LiXAYBZO(X+3Y+5Z) / 2, added to ethanol, and single crystal ternary powder is added, and then the solution is stirred at 45~60℃ until the solvent is completely evaporated, and the resulting mixture is calcined at 600~800℃ for 1~3h to obtain a LiXAYBZO(X+3Y+5Z) / 2 modified high nickel material.
[0077] In a third aspect, the present application proposes a positive electrode plate, comprising the positive electrode material in the above embodiment.
[0078] In some embodiments of the present application, the positive electrode plate includes a positive electrode current collector and a positive electrode coating coated on the positive electrode current collector. The positive electrode coating is formed by a positive electrode slurry. The positive electrode slurry includes a positive electrode active material, a binder and a conductive material. The binder includes polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, polyethylene, polypropylene, styrene-butadiene rubber, acrylic (ester) styrene-butadiene rubber, epoxy resin or nylon, etc., which are not limited in this application; the conductive material includes carbon black, acetylene black, Ketjen black, carbon fiber, carbon nanotubes, metal powder, metal fiber, copper, nickel, aluminum, silver or polyphenylene derivatives, etc., which are not limited in this application.
[0079] In some embodiments of the present application, a method for preparing a positive electrode sheet is also provided, and the steps are as follows: dissolving the positive electrode active material (the modified high-nickel ternary material provided in the present application), the conductive agent acetylene black, and the binder polyvinylidene fluoride (PVDF) in a solvent N-methylpyrrolidone (NMP) in a weight ratio of 96.5:1.5:2, and stirring and mixing them thoroughly to obtain a positive electrode slurry; then, the positive electrode slurry is evenly coated on a positive electrode current collector with a primer, and then dried, cold pressed, and cut to obtain a positive electrode sheet.
[0080] The positive electrode sheet proposed in the embodiment of the present application has all the beneficial effects of the positive electrode materials of the above embodiments, which will not be described in detail here.
[0081] In a fourth aspect, the present application provides a secondary battery comprising the positive electrode sheet in the above embodiment.
[0082] A secondary battery includes the positive electrode sheet described in the above embodiment, as well as a negative electrode sheet, a separator, and an electrolyte. A secondary battery can be a single battery cell. For example, a lithium-ion battery cell primarily relies on the movement of lithium ions between the positive and negative electrode sheets to function. In cylindrical battery cells, a three-layer thin film structure is wound into a cylindrical electrode assembly, while in rectangular battery cells, the thin film structure is wound or stacked into a roughly rectangular electrode assembly.
[0083] In a typical battery cell structure, the battery cell includes a casing, an electrode assembly, and an electrolyte. The electrode assembly is housed in the battery cell casing and includes a positive electrode sheet, a negative electrode sheet, and a separator. The casing includes an outer shell and end caps. The outer shell includes a housing formed by multiple walls and an opening. The end caps are arranged at the opening to seal the housing. In addition to the electrode assembly, the housing cavity also contains electrolyte. The positive and negative electrode sheets in the electrode assembly include tabs. To ensure that high currents can pass without melting, the positive electrode tabs are multiple and stacked together, and the negative electrode tabs are multiple and stacked together. The tabs are electrically connected to electrode terminals located outside the battery cell via connecting members. The electrode terminals generally include positive and negative electrode terminals. For rectangular battery cells, the electrode terminals are generally located on the end caps. Multiple battery cells are connected in series and / or in parallel via the electrode terminals for various applications.
[0084] A battery composed of cells assembled in a wound manner is called a wound battery. Wound batteries are also called cells, and those in the battery industry call them roll cores. Compared to flat-plate batteries, wound batteries are made by winding plates only about 1mm thick at high pressure. Through special processing methods, the battery has many unique features: super high-rate discharge capability, with a maximum discharge rate of 18C to 30C; excellent high and low temperature performance, capable of operating at -55°C to 150°C; stable high output voltage and higher energy density; sturdy structure with excellent seismic resistance; no free electrolyte (such as colloidal acid), allowing it to be placed in any direction for operation; fast charging, with a charge of over 95% in 40 minutes (1C charging); extremely long life, with a designed float charge life of over 8 years; and extremely high resistance to low-current deep discharge.
[0085] The electrolyte used in the present application may be an electrolyte known in the prior art, including an organic solvent, a lithium salt, and an additive; the isolation membrane used in the present application may be an isolation membrane known in the prior art.
[0086] The secondary battery proposed in this application has all the beneficial effects of the above-mentioned positive electrode materials, which will not be described in detail here.
[0087] Secondary batteries can be formed into battery modules. A battery module is constructed by electrically connecting a number of secondary batteries and enclosing them in a frame to protect them from external shock, heat, and vibration. A common battery module typically consists of two end plates, with multiple battery cells (secondary batteries) arranged between them. The end plate with the module's output terminal is called the output terminal plate, while the end plate without the output terminal is called the non-output terminal plate.
[0088] Secondary batteries can also be battery packs. In some battery production and processing technologies, multiple battery cells are first integrated into battery modules, and then the battery modules are encapsulated in a battery box to form a battery pack. A battery pack can encapsulate multiple battery modules in one row, or multiple rows of multiple battery modules. The arrangement of multiple rows of multiple battery modules can be double rows and multiple columns, multiple rows and double columns, or multiple rows and multiple columns. Taking a battery pack encapsulating double rows and multiple columns of battery modules as an example, the first end plate of each column is generally the head output extreme plate, the two adjacent end plates between the two rows of battery modules are the middle non-output extreme plates, and the last end plate of each column is the tail non-output extreme plate. The head output extreme plate and one of the middle non-output extreme plates belong to the first row of battery modules, and one of the middle non-output extreme plates and the tail output extreme plate belong to the second row of battery modules.
[0089] In a fifth aspect, the present application provides an electrical device comprising the secondary battery in the above embodiment.
[0090] The electrical devices proposed in this application include but are not limited to: mobile phones, portable devices, laptops, electric vehicles, ships, spacecraft, electric toys and electric tools, etc. For example, spacecraft include airplanes, rockets, space shuttles and spacecraft, etc. Electric toys include fixed or mobile electric toys, such as game consoles, electric vehicle toys, electric ship toys and electric airplane toys, etc. Electric tools include metal cutting power tools, grinding power tools, assembly power tools and railway power tools, such as electric drills, electric grinders, electric wrenches, electric screwdrivers, electric hammers, impact drills, concrete vibrators and electric planers.
[0091] The electrical device proposed in this application has all the beneficial effects of the above-mentioned positive electrode materials, which will not be described in detail here.
[0092] Below, the embodiment of the present application is described. The embodiment described below is exemplary and is only used to explain the present application, and is not to be construed as limiting the present application. Where specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. Reagents or instruments used that do not specify the manufacturer are conventional products that can be obtained commercially.
[0093] Example 1
[0094] (1) Preparation of single crystal LiNixCoyMnzO2: Soluble sulfates of nickel, cobalt and manganese are prepared into a solution with a total molar concentration of metal ions of 1.5 mol / L according to a certain molar ratio of nickel, cobalt and manganese ions (83:12:5). Then, a certain concentration of sodium hydroxide solution (concentration of 6 mol / L) and ammonia water (concentration of 0.3 mol / L) are added in sequence and stirred and mixed. The coprecipitation reaction is carried out under a nitrogen atmosphere. The pH value of the coprecipitation reaction is controlled to be 10 and the reaction temperature is controlled to be 55℃ to obtain a hydroxide precursor (Ni0.83Co0.12Mn0.05)(OH)2; the prepared hydroxide precursor was washed and dried, LiOH and KCl flux were added, first sintered at 500℃ for 6h, then calcined at 800℃ for 15h, and then annealed in oxygen at 600℃ for 3h to obtain single crystal LiNi0.83Co0.12Mn0.05O2 high nickel ternary material powder with Dv50≥4μm and SPAN≥1.6.
[0095] (2) Preparation of modified high-nickel materials: LiNO3, La(CH3COO)3 and C4H4NNbO9·nH2O in a stoichiometric ratio were added to ethanol as materials for preparing Li5La3Nb2O12, and single crystal ternary powder was added to control the total doping mass of lanthanum and niobium to be 1%. The solution was then stirred at 55°C until the solvent was completely evaporated, and the resulting mixture was calcined at 700°C for 3h to obtain a high-nickel material modified with 1wt% Li5La3Nb2O12 (denoted as LABO).
[0096] Example 2
[0097] The steps are basically the same as those in Example 1, except that in step (2), the total doping mass of lanthanum and niobium is controlled to be 3%.
[0098] Example 3
[0099] The steps are basically the same as those in Example 1, except that in step (2), the total doping mass of lanthanum and niobium is controlled to be 5%.
[0100] Example 4
[0101] The steps are basically the same as those in Example 1, except that in step (2), the total doping mass of lanthanum and niobium is controlled to be 10%.
[0102] Example 5
[0103] (1) Preparation of single crystal LiNixCoyMnzO2: Soluble sulfates of nickel, cobalt and manganese are prepared into a solution with a total molar concentration of metal ions of 1.0 mol / L according to a certain molar ratio of nickel, cobalt and manganese ions (85:10:5). Then, a certain concentration of sodium hydroxide solution (concentration of 4 mol / L) and ammonia water (concentration of 0.1 mol / L) are added in sequence and stirred. The coprecipitation reaction is carried out under a nitrogen atmosphere. The pH value of the coprecipitation reaction is controlled to be 9 and the reaction temperature is controlled to be 4. 0℃, a hydroxide precursor (Ni0.85Co0.10Mn0.05)(OH)2 was obtained; the prepared hydroxide precursor was washed and dried, LiOH and KCl flux were added, first sintered at 500℃ for 6h, then calcined at 800℃ for 15h, and then annealed in oxygen at 600℃ for 3h to obtain single crystal LiNi0.85Co0.10Mn0.05O2 high nickel ternary material powder with Dv50≥4μm and SPAN≥1.6.
[0104] (2) Preparation of modified high-nickel material: LiNO3 and C4H4NNbO9·nH2O in a stoichiometric ratio were added to ethanol as materials for preparing Li6Nb2O8, and single crystal ternary powder was added to control the niobium doping mass to be 3%. The solution was then stirred at 55°C until the solvent was completely evaporated, and the resulting mixture was calcined at 700°C for 3h to obtain a 3wt% Li6Nb2O8 (denoted as LBO) modified high-nickel material.
[0105] Example 6
[0106] (1) Preparation of single crystal LiNixCoyMnzO2: Soluble sulfates of nickel, cobalt and manganese were prepared into a solution with a total molar concentration of metal ions of 1.0 mol / L according to a certain molar ratio of nickel, cobalt and manganese ions (84:12:4). Then, a certain concentration of sodium hydroxide solution (4 mol / L) and ammonia water (0.1 mol / L) were added in sequence and stirred. The coprecipitation reaction was carried out under a nitrogen atmosphere. The pH value of the coprecipitation reaction was controlled to be 9 and the reaction temperature was controlled to be 4. 0℃, a hydroxide precursor (Ni0.84Co0.12Mn0.04)(OH)2 was obtained; the prepared hydroxide precursor was washed and dried, LiOH and KCl flux were added, first sintered at 500℃ for 6h, then calcined at 800℃ for 15h, and then annealed in oxygen at 600℃ for 3h to obtain single crystal LiNi0.84Co0.12Mn0.04O2 high nickel ternary material powder with Dv50≥4μm and SPAN≥1.6.
[0107] (2) Preparation of modified high-nickel materials: LiNO3 and C4H4NNbO9·nH2O in a stoichiometric ratio were added to ethanol as materials for preparing Li5La3O7, and single crystal ternary powder was added to control the lanthanum doping mass to be 3%. The solution was then stirred at 55°C until the solvent was completely evaporated, and the resulting mixture was calcined at 700°C for 3h to obtain a high-nickel material modified with 3wt% Li5La3O7 (denoted as LAO).
[0108] Example 7
[0109] (1) Preparation of single crystal LiNixCoyMnzO2: Soluble sulfates of nickel, cobalt and manganese are prepared into a solution with a total molar concentration of metal ions of 1.5 mol / L according to a certain molar ratio of nickel, cobalt and manganese ions (83:12:5). Then, a certain concentration of sodium hydroxide solution (concentration of 6 mol / L) and ammonia water (concentration of 0.3 mol / L) are added in sequence and stirred and mixed. The coprecipitation reaction is carried out under a nitrogen atmosphere. The pH value of the coprecipitation reaction is controlled to be 10 and the reaction temperature is controlled to be 55 ° C to obtain a hydroxide precursor (Ni0.83Co0.12Mn0.05)(OH)2; the prepared hydroxide precursor was washed and dried, LiOH and KCl flux were added, first sintered at 300 ° C for 7 hours, then calcined at 850 ° C for 16 hours, and then annealed in oxygen at 400 ° C for 4 hours to obtain single crystal LiNi0.83Co0.12Mn0.05O2 high nickel ternary material powder with Dv50≥4μm and SPAN≥1.6.
[0110] (2) Preparation of modified high-nickel materials: LiNO3 and C4H4NTiO9·nH2O in a stoichiometric ratio were added to ethanol as materials for preparing Li6Ti2O8, and single crystal ternary powder was added to control the titanium doping mass to be 3%. The solution was then stirred at 45°C until the solvent was completely evaporated, and the resulting mixture was calcined at 600°C for 3h to obtain a 3wt% Li6Ti2O8 (denoted as LBO) modified high-nickel material.
[0111] Example 8
[0112] (1) Preparation of single crystal LiNixCoyMnzO2: Soluble sulfates of nickel, cobalt and manganese are prepared into a solution with a total molar concentration of metal ions of 1.5 mol / L according to a certain molar ratio of nickel, cobalt and manganese ions (83:12:5). Then, a certain concentration of sodium hydroxide solution (concentration of 6 mol / L) and ammonia water (concentration of 0.3 mol / L) are added in sequence and stirred and mixed. The coprecipitation reaction is carried out under a nitrogen atmosphere. The pH value of the coprecipitation reaction is controlled to be 10 and the reaction temperature is controlled to be 55 ° C to obtain a hydroxide precursor (Ni0.83Co0.12Mn0.05)(OH)2; the prepared hydroxide precursor was washed and dried, LiOH and KCl flux were added, first sintered at 350 ° C for 6 hours, then calcined at 750 ° C for 14 hours, and then annealed in oxygen at 450 ° C for 4 hours to obtain single crystal LiNi0.83Co0.12Mn0.05O2 high nickel ternary material powder with Dv50≥4μm and SPAN≥1.6.
[0113] (2) Preparation of modified high-nickel materials: LiNO3 and Pr(CH3COO)3 in a stoichiometric ratio were added to ethanol as materials for preparing Li5Pr3O7, and single crystal ternary powder was added to control the doping mass of praseodymium to be 3%. The solution was then stirred at 50°C until the solvent was completely evaporated, and the resulting mixture was calcined at 650°C for 2h to obtain a high-nickel material modified with 3wt% Li5Pr3O7 (denoted as LAO).
[0114] Example 9
[0115] (1) Preparation of single crystal LiNixCoyMnzO2: Soluble sulfates of nickel, cobalt and manganese are prepared into a solution with a total molar concentration of metal ions of 1.5 mol / L according to a certain molar ratio of nickel, cobalt and manganese ions (83:12:5). Then, a certain concentration of sodium hydroxide solution (concentration of 6 mol / L) and ammonia water (concentration of 0.3 mol / L) are added in sequence and stirred and mixed. The coprecipitation reaction is carried out under a nitrogen atmosphere. The pH value of the coprecipitation reaction is controlled to be 10 and the reaction temperature is controlled to be 55 ° C to obtain a hydroxide precursor (Ni0.83Co0.12Mn0.05)(OH)2; the prepared hydroxide precursor was washed and dried, LiOH and KCl flux were added, first sintered at 400 ° C for 5 hours, then calcined at 700 ° C for 18 hours, and then annealed in oxygen at 550 ° C for 3 hours to obtain single crystal LiNi0.83Co0.12Mn0.05O2 high nickel ternary material powder with Dv50≥4μm and SPAN≥1.6.
[0116] (2) Preparation of modified high-nickel materials: LiNO3, Ce(CH3COO)3 and C4H4NZrO9·nH2O in a stoichiometric ratio were added to ethanol as materials for preparing Li5Ce3Zr2O12, and single crystal ternary powder was added to control the total doping mass of cerium and zirconium to be 3%. The solution was then stirred at 60°C until the solvent was completely evaporated, and the resulting mixture was calcined at 750°C for 2h to obtain a 3wt% Li5Ce3Zr2O12 (denoted as LABO) modified high-nickel material.
[0117] Example 10
[0118] (1) Preparation of single crystal LiNixCoyMnzO2: Soluble sulfates of nickel, cobalt and manganese are prepared into a solution with a total molar concentration of metal ions of 1.5 mol / L according to a certain molar ratio of nickel, cobalt and manganese ions (83:12:5). Then, a certain concentration of sodium hydroxide solution (concentration of 6 mol / L) and ammonia water (concentration of 0.3 mol / L) are added in sequence and stirred and mixed. The coprecipitation reaction is carried out under a nitrogen atmosphere. The pH value of the coprecipitation reaction is controlled to be 10 and the reaction temperature is controlled to be 55℃ to obtain a hydroxide precursor (Ni0.83Co0.12Mn0.05)(OH)2; the prepared hydroxide precursor was washed and dried, LiOH and KCl flux were added, first sintered at 450℃ for 5h, then calcined at 900℃ for 12h, and then annealed in oxygen at 600℃ for 2h to obtain single crystal LiNi0.83Co0.12Mn0.05O2 high nickel ternary material powder with Dv50≥4μm and SPAN≥1.6.
[0119] (2) Preparation of modified high-nickel materials: LiNO3, Yb(CH3COO)3 and C4H4NMoO9·nH2O in a stoichiometric ratio are added to ethanol as materials for preparing Li5Yb3Mo2O12 (X≥5, Y≥3, Z≥2, and X, Y, Z are all integers, A is ytterbium, B is molybdenum), and single crystal ternary powder is added to control the total doping mass of ytterbium and molybdenum to be 3%. The solution is then stirred at 50°C until the solvent is completely evaporated, and the resulting mixture is calcined at 800°C for 1 h to obtain a 3wt% Li5Yb3Mo2O12 (denoted as LABO) modified high-nickel material.
[0120] Comparative Example 1
[0121] Preparation of single crystal LiNixCoyMnzO2: Soluble sulfates of nickel, cobalt and manganese are prepared into a solution with a total molar concentration of metal ions of 1.5 mol / L according to a certain molar ratio of nickel, cobalt and manganese ions (83:12:5). Then, a certain concentration of sodium hydroxide solution (concentration of 6 mol / L) and ammonia water (concentration of 0.3 mol / L) are added in sequence and stirred and mixed. Co-precipitation reaction is carried out under nitrogen atmosphere. The pH value of the co-precipitation reaction is controlled to be 10 and the reaction temperature is 55 ℃ to obtain a hydroxide precursor (Ni0.83Co0.12Mn0.05)(OH)2; the prepared hydroxide precursor was washed and dried, LiOH and KCl flux were added, first sintered at 500℃ for 6h, then calcined at 800℃ for 15h, and then annealed in oxygen at 600℃ for 3h to obtain single crystal LiNi0.83Co0.12Mn0.05O2 high nickel ternary material powder with Dv50≥4μm and SPAN≥1.6.
[0122] The modified high-nickel materials obtained in Examples 1-10 and the high-nickel material obtained in Comparative Example 1 were made into positive electrode sheets, and further assembled into synthetic lithium-ion batteries to test relevant performance. The specific methods and results are as follows:
[0123] (1) Preparation of negative electrode sheet:
[0124] The active material graphite, silicon, conductive agent acetylene black, high molecular polymer, and thickener sodium carboxymethyl cellulose (CMC) are dissolved in deionized water in a weight ratio of 90:5:2:2:1, and evenly mixed to prepare a negative electrode slurry. The negative electrode slurry is coated on copper foil, dried, and then cold-pressed and cut to obtain negative electrode sheets.
[0125] (2) Preparation of positive electrode sheet:
[0126] The positive electrode active material (the high nickel material prepared in Examples 1-10 and Comparative Example 1), the conductive agent acetylene black, and the binder polyvinylidene fluoride (PVDF) were dissolved in a solvent N-methylpyrrolidone (NMP) at a weight ratio of 96.5:1.5:2, and the mixture was thoroughly stirred and mixed to obtain a positive electrode slurry. The positive electrode slurry was evenly coated on the positive electrode current collector with a primer, and then dried, cold pressed, and cut to obtain a positive electrode sheet.
[0127] (3) Isolation film:
[0128] The diaphragm is a PE diaphragm with PVDF and alumina coating on the surface to improve adhesion and heat resistance.
[0129] (4) Electrolyte:
[0130] The electrolyte is prepared by mixing ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) in a volume ratio of 1:1:1, and then evenly dissolving LiPF6:LiFSI (2:8) in the above solution. The concentration of the lithium salt in this electrolyte is 1 mol / L.
[0131] (5) Lithium-ion battery assembly:
[0132] The positive electrode sheet, separator, and negative electrode sheet are stacked in order, with the separator placed between the positive and negative sheets to provide insulation. The cells are then wound to form bare cells, with tabs welded to the cells. The cells are then placed in aluminum shells and baked at 80°C to remove moisture. Electrolyte is then injected and sealed to create an uncharged battery. The uncharged battery then undergoes a series of processes, including resting, hot and cold pressing, formation, shaping, and capacity testing, to produce a lithium-ion battery product.
[0133] (6) Performance testing:
[0134] 1. Capacity test:
[0135] ① Let it stand for 30 minutes;
[0136] ② Charge at a rate of 1 / 3C to 4.25V, then charge at a constant voltage of 4.25V to 0.05C;
[0137] ③Let it stand for 30 minutes;
[0138] ④Discharge at a rate of 1 / 3C to 2.8V, obtaining the capacity C0;
[0139] The energy obtained is the battery energy, and the weight energy density = energy / battery weight.
[0140] 2. DCR test:
[0141] The prepared secondary battery was placed at 25°C for 30 minutes, charged to 4.25V at a rate of 1 / 3C, and ended at a constant voltage of 0.05C; placed at rest for 10 minutes, and then discharged at a rate of 1 / 3C0 until the battery cell's capacity was 10% of the full charge, which is called 10% SOC; placed at rest for 60 minutes, and discharged at a rate of 4C0 for 10 seconds, and the DCR value of the battery cell was recorded.
[0142] 3. Storage test:
[0143] ① Place the fresh battery cell at room temperature for 30 minutes;
[0144] ② Charge at a rate of 1 / 3C to 4.25V, then charge at a constant voltage of 4.25V to 0.05C;
[0145] ③Let it stand for 30 minutes;
[0146] ④Discharge at a rate of 1 / 3C to 2.8V, obtaining the capacity C0;
[0147] ⑤Store at 60℃ and 97% SOC, take out and test once every 10 days. The capacity is Cn, until Cn decays to 80% C0, and the corresponding storage days are obtained.
[0148] 4. Element doping test: Analyzed by inductively coupled plasma (ICP) spectroscopy, refer to relevant test standards YS / T 1006.2-2014, GB / T 23367.2-2009 or YS / T 1028.5-2015.
[0149] 5. Cycle test:
[0150] ① Adjust the temperature to 25℃ and keep warm for 2 hours;
[0151] ②Let it stand for 5 minutes;
[0152] ③ Charge at a rate of 1 / 3C to 4.3V, then charge at a constant voltage of 4.3V to 0.05C;
[0153] ④Let it stand for 5 minutes;
[0154] ⑤Discharge to 2.8V at a rate of 1 / 2C0;
[0155] ⑥Let it stand for 5 minutes;
[0156] ⑦ Repeat steps ③, ④, ⑤, and ⑥ until the capacity fading ≤ 80% to obtain the corresponding cycle life.
[0157] The test results are shown in Table 2 below.
[0158] In Table 2 , the step ranges of energy density are defined as: moderate 258–260 Wh / kg, moderate 260–262 Wh / Kg, and high 262–264 Wh / Kg;
[0159] In Table 2, the DCR step range is defined as: low 0.8~1.0mΩ, moderate 1.0~1.2mΩ, high 1.2~1.4mΩ, and high 1.4~1.6mΩ.
[0160] Table 2 Performance tests of various embodiments and comparative examples Doping amount adulterants Single crystal size Dv50 (4μm) Energy density (Wh / Kg) 25℃ 10%SOC DCR (mΩ) 25℃ 2.8-4.3V cycle life (cycles) 60℃ 4.3V storage (days) Comparative Example 1 - - 5 high high 1200 280 Example 1 1% LABO 5 High Moderate 2000 500 Example 2 3% LABO 5 high Low 2500 900 Example 3 5% LABO 5 high Low 2200 800 Example 4 10% LABO 5 Moderate High 2000 700 Example 5 3% LBO 5 high High 1900 600 Example 6 3% LAO 5 high Low 1600 800 Example 7 3% LBO 5 high High 1900 600 Example 8 3% LAO 5 high Low 1600 800 Example 9 3% LABO 5 high Low 2500 900 Example 10 3% LABO 5 high Low 2500 900
[0161] As can be seen from Table 2, the doping of the lanthanide element La in Example 5 can improve kinetics, reduce DCR, enhance structural stability, and improve cycling and storage performance; the doping of metallic Nb in Example 8 can improve bulk structural stability and enhance cycling and storage performance, but both are more advantageous than the co-doping of two metal elements in Example 4. In Examples 7-10, replacing the lanthanide element La with a metal element within the scope of other solutions, and / or replacing metallic Nb with another metal element within the scope of the solution, can achieve the effect of improving cycling performance and storage performance.
[0162] The above are only preferred embodiments of the present application and are not intended to limit the scope of the present invention. Various modifications and variations are possible for those skilled in the art. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application shall be included in the scope of the present invention.
Claims
1. A positive electrode material, characterized in that The positive electrode material includes positive electrode material particles, and the positive electrode material particles include a matrix and a modifying element, wherein: The matrix includes LiNixCoyMnzO2, x≥0.8, y≤0.12, x+y+z=1; The modifying elements include rare earth elements and / or refractory metal elements.
2. The positive electrode material according to claim 1, wherein The rare earth element is at least partially located on the surface of the substrate; and / or, The refractory metal element is at least partially located inside the matrix.
3. The positive electrode material according to claim 1, wherein The rare earth element includes at least one of lanthanum, cerium, praseodymium, neodymium, promethium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium, and lutetium; and / or, The refractory metal element includes at least one of titanium, zirconium, niobium, vanadium, molybdenum and tungsten.
4. The positive electrode material according to claim 1, wherein The rare earth element is lanthanum; and / or, The refractory metal element is niobium.
5. The positive electrode material according to claim 1, wherein The modifying element is combined with the matrix by doping.
6. The positive electrode material according to claim 1, wherein Based on the mass of the positive electrode material being 100%, the doping mass of the modifying element is 1-10%.
7. The positive electrode material according to claim 1, wherein Based on the mass of the positive electrode material being 100%, the doping mass of the modifying element is 3-5%.
8. The positive electrode material according to claim 1, wherein The LiNixCoyMnzO2 is a single crystal particle.
9. The positive electrode material according to claim 1, wherein The Dv50 of the LiNixCoyMnzO2 is ≥ 4 μm; and / or The SPAN of the LiNixCoyMnzO2 is ≥1.
6.
10. A method for preparing a positive electrode material according to any one of claims 1 to 9, characterized in that: The following steps are involved: The modifier is mixed with LiNixCoyMnzO2 and calcined to obtain the positive electrode material; wherein, In the LiNixCoyMnzO2, x≥0.8, y≤0.12, x+y+z=1; The modifier includes rare earth elements and / or refractory metal elements.
11. The method for preparing the positive electrode material according to claim 10, wherein: The modifier includes LiXAYBZO(X+3Y+5Z) / 2, LiXAYO(X+3Y) / 2 or LiXBZO(X+5Z) / 2, X≥5, Y≥3, Z≥2, and X, Y, and Z are all integers, A is any one of lanthanum, cerium, praseodymium, neodymium, promethium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium, and lutetium, and B is any one of titanium, zirconium, niobium, vanadium, molybdenum, and tungsten.
12. The method for preparing the positive electrode material according to claim 10, wherein: The calcination temperature is 600-800° C. and the calcination time is 1-3 hours.
13. A positive electrode plate, characterized in that: The positive electrode sheet comprises the positive electrode material according to any one of claims 1 to 9.
14. A secondary battery, characterized in that: The secondary battery includes the positive electrode sheet as claimed in claim 13.
15. An electrical device, characterized in that: The electric device includes the secondary battery according to claim 14 .
Citation Information
Patent Citations
Rare-earth doping modified lithium ion battery ternary positive electrode material and preparation method thereof
CN103855384A
Continuous production method and device for in-situ doping of high-nickel ternary positive electrode material precursor of lithium ion battery
CN113387400A
Preparation method of nanoscale LLZO coated high-nickel positive electrode material
CN114394632A
Positive electrode active material, nonaqueous secondary battery, and method for manufacturing positive electrode active material
JP2019003786A
Cited By
Composite coated ultra-high nickel positive electrode material as well as preparation method and application thereof
CN120600785A
